Type 2 Diabetes: Demystifying the Global Epidemic - Unnikrishnan, Ranjit; Pradeepa, Rajendra; Joshi, Shashank R.; Mohan, Viswanathan (Diabetes (New York, N.Y.), 2017)
Type 2 diabetes (T2D) has attained the status of a global pandemic, spreading from affluent industrialized nations to the emerging economies of Asia, Latin America, and Africa. There is significant global variation in susceptibility to T2D, with Pacific Islanders, Asian Indians, and Native Americans being considerably more prone to develop the disorder. Although genetic factors may play a part, the rapidity with which diabetes prevalence has risen among these populations reflects the far-ranging and rapid socioeconomic changes to which they have been exposed over the past few decades. Traditionally, obesity and its correlate, insulin resistance, have been considered the major mediators of T2D risk; however, recent evidence shows that early loss of β-cell function plays an important role in the pathogenesis of T2D, especially in nonobese individuals such as South Asians. Knowledge of the modifiable risk factors of T2D is important, as it forms the basis for designing cost-effective preventive and therapeutic strategies to slow the epidemic in populations at increased risk. Lessons learned from randomized prevention trials need to be implemented with appropriate cultural adaptations, accompanied by empowerment of the community, if the diabetes epidemic is to be slowed or halted.